Effect of Catalyst Layer and Fuel Utilization on the Durability of Direct Methane SOFC. (21st September 2015) - Georges, Samuel; Nóbrega, Shayenne D.; Cheah, Seng Kian; Steil, M. C.; Bultel, Yann; Rieu, Mathilde; Viricelle, Jean-Paul; Gelin, Patrick
Abstract : Solid oxide fuels cells with and without anodic catalytic layer and specific anodic current collectors were developed in order to be fueled by dry methane. Due to the cell architecture integrating a 0.1wt% Ir-CGO catalyst layer onto the anode, platinum, gold and cupper screen-printed meshes were designed and optimized to ensure efficient current collection between the anode surface and the catalyst membrane. Current density and ageing in H2 and in pure dry CH4 respectively were compared to conventional pressed grid collecting systems. Similar performances were achieved using bulk grids or gold, platinum and copper screen-printed meshes. Operation in pure dry methane is compared with and without the catalytic layer as a function of the fuel utilization. It is demonstrated that long term operation is possible provided that sufficient faradic efficiency is achieved.